PAGES FROM NAGYVÁRAD CITY’S FOOTBALL HISTORY (1901 – 1919) - LUKÁCS, Norbert Csaba (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
In the first part, the paper refers to the events which led to the establishment of the first sports associations of Nagyvárad city, followed by the presentation of the school sports associations and clubs that had football departments, the football fields, the very first round-ball game in the city’s history, and the attendance of the teams to regional football championships. Within the documentation phase, I consulted specialized books, monographs, encyclopedias and sports sections of newspapers published in Oradea referring to the studied topic. Article history: Received 2022 August 08; Revised 2022 September 20; Accepted 2022 September 21; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. File din istoria fotbalului orașului Nagyvárad (1901 – 1919). În prima parte, lucrarea se referă la evenimentele care au condus la constituirea primelor asociații sportive din orașul Nagyvárad după care sunt prezentate asociațiile și cluburile sportive școlare cu secții de fotbal, terenurile de fotbal, primul meci cu balonul rotund din istoria orașului și participarea echipelor în campionatele regionale de fotbal. În cadrul activității de documentare am consultat cărți de specialitate, lucrări monografice, enciclopedii și rubricile de sport din presa orădeană care se referă la tema studiată. Cuvinte cheie: fotbal, asociație sportivă, Nagyvárad, Oradea.